Where is Area 51? - Manzanero, Paula, 1962-; Foley, Tim, 1962- (New York : Penguin Workshop, 2018)
Describes the isolated Nevada air base known as Area 51, covering its use for testing top-secret aircraft, and discusses speculation about a connection to unidentified flying objects.
Where is Area 51? -- Just a space on the map -- Gathering intelligence -- The Roswell connection -- The Cold War heats up -- UFOs or US aircraft? -- The Air Force strikes back -- Conspiracies -- The box -- Is there an Area 52? -- Area 51 today -- Timeline of Area 51 -- Timeline of the world.
Includes bibliographical references.
7.4.
3-6.
1080L
Includes a pull-out map.
X
Keywords: Area 51 (Nev.) -- Juvenile literature; Air bases -- Nevada -- Juvenile literature; Research aircraft -- United States -- Juvenile literature; Unidentified flying objects -- Juvenile literature; Area 51 (Nev.); Air bases; Research aircraft; Unidentified flying objects